The effect of Cu exposure on the bioaccumulation of Zn and antioxidant activities in different parts of Centella asiatica. - Ong, G.H.; Yap, Chee Kong; Mahmood, Maziah; Tan, Soon Guan (EM International, 2011)

(untitled)
This study was carried out by using Centella asiatica grown using a hydroponic system under laboratory conditions to determine the effects of Cu exposure on Zn accumulation and antioxidant activities of the plant. The antioxidant activities include superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX) and guaiacol peroxidase (GPX). The treatments Zn2ppm+Cu0.1ppm and Zn6ppm+Cu0.5ppm reduced the accumulation of Zn in leaves but increased the uptake in roots (Zn6ppm+Cu0.5ppm). This showed that Cu and Zn acted antagonistically to each other in leaves but synergistically on each other in roots. GPX, APX and SOD activity in leaves were increased while in roots only GPX and SOD activity were increased when Zn was added together with Cu. Therefore, SOD and GPX could be used as biomarkers to monitor the toxicity of Cu and Zn in C. asiatica.